The Complete React Developer Course (with Hooks and Redux) - Mead, Andrew (Packt Publishing, 2019)
Learn how to build and launch React web applications using React, Redux, Webpack, React-Router, and more! About This Video Build and launch React web applications using React, Redux, Webpack, React-Router Learn the latest React libraries and tools In Detail The Complete React Developer Course (with Hooks and Redux) starts with the fundamentals and covers everything you'll need to build, and launch React web apps. You'll see what it takes to build and launch a React app, from the first line of code to the final production deployment. This course was designed with one goal: to turn you into a professional React developer capable of developing, testing, and deploying real-world production applications. You'll learn React by doing, not watching. From the first videos, you'll build each project and resolve programming challenges designed to test and reinforce what you've learned. Throughout the course you'll build two React web apps: The first app, a decision-making app called Indecision, is our starter application. You'll learn React fundamentals while learning exactly what it takes to get a React app up-and-running. The second app, an expense manager called Budget, has all the features you'd expect from a real application. You'll set up authentication, user accounts, routing, testing, form validation, database storage, and more.
Online resource; Title from title screen (viewed October 17, 2019)
Keywords: Electronic videos